Anti-Inflamatory Activity Evaluation of Sungkai Leaf Ethanol Extract (Peronema Canescens Jack) Using the Red Blood Cell Membrane Stabilization Method - Aria, Mimi; Nessa, Nessa; Ilona, Sandra; Lestari, Wahyu (PT. Riset Press International, 2025)
Research has been carried out on the anti-inflammatory activity test of the ethanol extract of Sungkai leaf (Peronema canescens Jack) with the red blood cell membrane stabilization method. Purpose of study was to determine the anti-inflammatory activity the effect of the concentration of ethanol extract of sungkai leaves. Anti-inflammatory activity can be determined by measuring stability red blood cells, looking at absorbance of decomposition of hemoglobin so that the percentage of stability is obtained. Variations in the concentration of the test solution made were 4 variations in concentration, namely 15, 30, 60 and 120 ppm. The extract's ability to reduce inflammation. was then compared standard ibuprofen. Based on the study's findings, the percentage of erythrocyte membrane stability of sungkai leaf extract sequentially with concentrations of 15, 30, 60 and 120 ppm was 2.24%, 32.61%, 37.72%, 44.31%, while the comparison (ibuprofen) The percentage of erythrocyte membrane stability, respectively, with concentrations of 15, 30, 60 and 120 ppm were 24.1%, 36.2%, 49.4%, 63.4% and control 0.98%. The data from study were analyzed using one-way ANOVA which was followed by Duncan test. From this research is isconcluded The activity that reduces inflammation of the ethanolic extract of the sungkai leaf variation of the concentration regarding ethanolic extract of sungkai leaf (Peronema canescens Jack) gave an influence on the anti-inflammatory activity with an increase in the proportion of the stability of the red blood cell membrane following The rise in the concentration of the ethanol extractf the sungkai leaf.